Visual deficits in a mouse model of Fetal alcohol spectrum disorders - Lantz, Crystal L.; Pulimood, Nisha S.; Rodrigues-Junior, Wandilson S.; Chen, Ching-Kang J.; Kalatsky, Valery A.; Manhaes, Alex C.; Medina, Alexandre E. (Frontiers in Pediatrics, 2014)
Alcohol consumption during pregnancy can lead to a multitude of neurological problems in offspring, varying from subtle behavioral changes to severe mental retardation. These alterations are collectively referred to as Fetal Alcohol Spectrum Disorders (FASD). Early alcohol exposure can strongly affect the visual system and children with FASD can exhibit an amblyopia-like pattern of visual acuity deficits even in the absence of optical and oculormotor disruption. Here we test whether early alcohol exposure can lead to a disruption in visual acuity, using a model of FASD to mimic alcohol consumption in the last months of human gestation. To accomplish this, mice were exposed to ethanol (5g/kg i.p) or saline on postnatal days (P) 5, 7 and 9. Two to three weeks later we recorded visually evoked potentials (VEPs) to assess spatial frequency detection and contrast sensitivity, conducted electroretinography (ERGs) to further assess visual function and imaged retinotopy using optical imaging of intrinsic signals. We observed that animals exposed to ethanol displayed spatial frequency acuity curves similar to controls. However, ethanol-treated animals showed a significant deficit in contrast sensitivity. Moreover, ERGs revealed a market decrease in both a- and b- waves amplitudes, and optical imaging suggest that both elevation and azimuth maps in ethanol-treated animals have a 10-20o greater map tilt compared to saline-treated controls. Overall, our findings suggest that binge alcohol drinking restricted to the last months of gestation in humans can lead to marked deficits in visual function.